Block of transmitter release by botulinum C1 action on syntaxin at the squid giant synapse - Marsal, Jordi (The National Academy of Sciences of the USA, 1997)
Electrophysiological, morphological, and biochemical approaches were combined to study the effect of the presynaptic injection of the light chain of botulinum toxin C1 into the squid giant synapse. Presynaptic injection was accompanied by synaptic block that occurred progressively as the toxin filled the presynaptic terminal. Neither the presynaptic action potential nor the Ca(2+) currents in the presynaptic terminal were affected by the toxin. Biochemical analysis of syntaxin moiety in squid indicates that the light chain of botulinum toxin C1 lyses syntaxin in vitro, suggesting that this was the mechanism responsible for synaptic block. Ultrastructure of the injected synapses demonstrates an enormous increase in the number of presynaptic vesicles, suggesting that the release rather than the docking of vesicles is affected by biochemical lysing of the syntaxin molecule.